Auditoria financiera a los estados financieros de "liga deportiva universitaria de la ciudad de Loja", en el periodo 2017 - Rugel Dávila, Luis Miguel (2020)
This thesis work entitled FINANCIAL AUDIT TO THE FINANCIAL STATEMENTS OF "UNIVERSITY SPORTS LEAGUE OF THE CITY OF LOJA", IN THE PERIOD 2017., was carried out with the purpose of ruling on the reasonableness of the financial statements prepared by the administration of the entity, in order to provide a tool that helps better decision making. The study was justified, since it has a theoretical and practical basis, with legal and conceptual basis of the audit, the legal framework, current regulations and the financial audit process, through the development of each of its phases. Based on the application of the financial audit methodology, the case study is developed by applying all its phases through tests and procedures, starting with preliminary planning, which allows us to obtain a general knowledge about the entity, then at the stage of specific planning, work programs by component are designed, which are developed in the execution stage obtaining sufficient, competent and relevant evidence to support the findings found, ending with the communication of results through a report containing an opinion where the opinion is recorded , complementary financial information and the results of the audit. 4 Thus, it was determined that for the Current Assets component of the Bank account, the cash of the company is not deposited daily in the bank's current account; several accounts of horros are managed in different financial institutions; there are no endorsements of income or expenditures on deposit vouchers, the source of funds and destinations are not determined); there are no Bank reconciliations; in the non-current Assets Property Plant and Equipment the depreciations and codifications corresponding to the assets held by the entity were not affected; in the Accounts Payable Liabilities; The accountant does not make timely payments to Municipalities for sports shows; There is no adequate control of taxes; Timely payments of salaries to employees and players are not made. In the expense accounts the most significant established differences are the Salaries to Players, it presents a reveling difference that has not been justified.